(untitled) (Research Nepal Journal of Development Studies, 2018)
The study of socio-economic impact of pilgrimage tourism in Janakpur shows the adverse effects in culture and environments. The study recommends to manage the devotee tourists more scientifically in top festivals. Many tourists are entering Nepal for religious purpose. This study has been concentrated on pilgrimage tourism and its socio-economic impacts in Janakpur area. Janaki mandir is one of the important religious sites of Nepal located in Dhanusha district which is around 234 KM far from the Kathmandu. In this connection how and why pilgrimage tourism brings socio economic changes in Janakpur area as well as what types of negative and positive impacts can be seen in the area. This study is based on both primary and secondary data and followed qualitative research design. For this study data were collected by using observation and individual questionnaires as data collection tools.